In Media We Trust? A Comparative Analysis of News Trust in New Zealand and Other Western Media Markets - Myllylahti, Merja; Treadwell, Greg (Informa UK Limited, 2021)
In the age of misinformation, trust and trustworthiness – core values of journalism – have become more important as news companies reeling from the pandemic seek emergency funding for their operations from the public and funders look for trusted brands to support. Earlier studies indicated people are more willing to pay for trusted news brands, and recently, the public funding of news has been directed to institutions that are regarded as trustworthy news outlets, and provide information that is in the public interest. While the concept of trust is complicated and measuring it is challenging, trust has rapidly become a key inquiry in academia. However, New Zealand lacks in this research, and this study aims to start to fill that gap. The paper is based on our survey of 1204 New Zealanders, and comparable data from 38 countries surveyed in the Reuters Digital News Report 2019. The paper finds that trust in news in New Zealand is high when compared internationally, but a large proportion (47%) of citizens don’t trust the news. It also finds New Zealanders are more concerned about misinformation and disinformation than respondents in other Western societies.
Keywords: Trust; Trustworthiness; News; Journalism; Aotearoa New Zealand